Pengaruh Penggunaan Media Menjahit Kreasi terhadap Keterampilan Pra Menulis Anak Usia 4–5 Tahun di TK Islam Mutiara Karawang Timur - Muhalisiah, Mutia; Darmiyanti, Astuti; Nirmala, Ine (Lembaga Yasin AlSys, 2025)
The low level of pre-writing skills among 4–5-year-old children at TK Islam Mutiara, East Karawang, is the central issue addressed in this study. The objective is to determine the difference in pre-writing abilities before and after the implementation of a creative sewing activity. This research employed a quantitative approach with a One Group Pretest-Posttest Design, which measures the same group before and after the intervention. The study population consisted of all 30 children in Group A, with a sample of 16 selected through purposive sampling based on specific criteria. Data were collected through a pretest, eight sewing activity sessions as treatment, and a posttest. The analysis results show an increase in the average pre-writing skill score from 42.00 (pretest) to 68.06 (posttest). A hypothesis test using the Paired Sample t-Test yielded a t value of 40.188 > t table value of 2.131, indicating a significant difference between the scores before and after the intervention. Thus, the creative sewing activity was proven to have a positive and significant impact on improving pre-writing skills in early childhood. The study’s implications highlight the importance of integrating fine motor activities, such as creative sewing, into the learning process to effectively and practically support children's writing readiness.